2015
DOI: 10.1016/j.ehb.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Retirement and cognitive development in the Netherlands: Are the retired really inactive?

Abstract: This paper uses longitudinal data to analyze the relation between retirement and cognitive development in the Netherlands. Controlling for individual fixed effects and lagged cognition, we find that retirees face lower declines in their cognitive flexibility than those who remain employed, which appears to be persistent 6 years after retirement. However, the information processing speed of low-educated retirees declines faster. The magnitude of both changes in cognition is such that retirees appear 5-6 years y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 49 publications
2
15
1
Order By: Relevance
“…In fact, retirement systematically undermines possible efforts to maintain the control abilities under biological challenge by eliminating various (job-related) sources of uncertainty and surprise, cutting substantial parts of the social network, at least for a substantial part of the day, and by possibly taking away opportunities for physical practice (depending on the job). Indeed, there is ample evidence that retirement is specifically associated with a general loss of processing speed ( de Grip et al, 2015 ) and general cognitive functioning ( Bonsang et al, 2012 ). Retirement selectively increases the rate of decline of cognitive abilities, presumably due to a lack of motivation to invest in compensatory activities ( Mazzonna and Peracchi, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, retirement systematically undermines possible efforts to maintain the control abilities under biological challenge by eliminating various (job-related) sources of uncertainty and surprise, cutting substantial parts of the social network, at least for a substantial part of the day, and by possibly taking away opportunities for physical practice (depending on the job). Indeed, there is ample evidence that retirement is specifically associated with a general loss of processing speed ( de Grip et al, 2015 ) and general cognitive functioning ( Bonsang et al, 2012 ). Retirement selectively increases the rate of decline of cognitive abilities, presumably due to a lack of motivation to invest in compensatory activities ( Mazzonna and Peracchi, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bonsang et al ( 2012 ), using data from the HRS, reached a similar conclusion following a similar approach. de Grip et al ( 2015 ), using Dutch data from the Maastricht Aging Study, found large negative effects of retirement on cognitive decline for some (but not all) measures of cognition included in their data set. Finally, Coe et al ( 2012 ), also using HRS data, used early retirement offers (which are legally required to be nondiscriminatory) as a source of exogenous variation, and found no support that retirement affects cognition.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…Among them, retirement from income-generating activities and reduced social participation pose a significant risk of cognitive loss in old age [1, 2]. Cognitive performance has long been studied to determine the threshold age of retirement, predominantly in the developed nations [35]. In a developing nation like India, greying of the population has an economic implication in terms of ascertaining the appropriate age for retirement [6–8].…”
Section: Introductionmentioning
confidence: 99%
“…Forced participation in employment in old age can be potent enough to alter the process of healthy aging among the fast-growing elderly population [16, 17]. Low-grade occupation is associated with poor educational attainment, which leads to a higher cognitive decline during old age [5]. Besides retirement from financial activities, reduced participation in social activities increases the risk of cognitive impairment in later life [2, 18, 19].…”
Section: Introductionmentioning
confidence: 99%